How well do blood folate concentrations predict dietary folate intakes in a sample of Canadian lactating women exposed to high levels of folate? An observational study - Sherwood Kelly L; Houghton Lisa A; O'Connor Deborah L (BMC, 2007)
Abstract Background In 1998, mandatory folic acid fortification of white flour and select cereal grain products was implemented in Canada with the intention to increase dietary folate intakes of reproducing women. Folic acid fortification has produced a dramatic increase in blood folate concentrations among reproductive age women, and a reduction in neural tube defect (NTD)-affected pregnancies. In response to improved blood folate concentrations, many health care professionals are asking whether a folic acid supplement is necessary for NTD prevention among women with high blood folate values, and how reliably high RBC folate concentrations predict folate intakes shown in randomized controlled trials to be protective against NTDs. The objective of this study was to determine how predictive blood folate concentrations and folate intakes are of each other in a sample of well-educated lactating Canadian women exposed to high levels of synthetic folate. Methods The relationship between blood folate concentrations and dietary folate intakes, determined by weighed food records, were assessed in a sample of predominantly university-educated lactating women (32 ± 4 yr) at 4-(n = 53) and 16-wk postpartum (n = 55). Results Median blood folate concentrations of all participants were well above plasma and RBC folate cut-off levels indicative of deficiency (6.7 and 317 nmol/L, respectively) and all, except for 2 subjects, were above the cut-off for NTD-risk reduction (>906 nmol/L). Only modest associations existed between total folate intakes and plasma (r = 0.46, P < 0.001) and RBC (r = 0.36, P < 0.01) folate concentrations at 16-wk postpartum. Plasma and RBC folate values at 16-wk postpartum correctly identified the quartile of folate intake of only 26 of 55 (47%) and 18 of 55 (33%) of subjects, respectively. The mean RBC folate concentration of women consuming 151-410 μg/d of synthetic folate (2nd quartile of intake) did not differ from that of women consuming >410 μg/d (3rd and 4th quartile). Conclusion Folate intakes, estimated by food composition tables, and blood folate concentrations are not predictive of each other in Canadian lactating women exposed to high levels of folate. Synthetic intakes > 151-410 μg/d in these women produced little additional benefit in terms of maximizing RBC content. More studies are needed to examine the relationship between blood folate concentration and NTD risk. Until data from such studies are available, women planning a pregnancy should continue to consume a daily folic acid supplement of 400 μg.